HUBUNGAN KEMAHIRAN PETERNAK TERHADAP EFISIENSI REPRODUKSI SAPI PERAH DI KUD SUKA MULYA KECAMATAN WATES KABUPATEN KEDIRI - Hasan Syafaat; Endang Sapta H.S; Nur Hafid (Universitas Islam Kadiri, 2018)
The research aims to find out how much the influence of breeder’s skills on the reproductive efficiency of dairy cattle at KUD suka mulya Wates subdistrict. The study was carried out using explanatory (correlational) methods. There are 2 research variables namely, the independent variable is farmers skills and the dependent variable are the reproductive efficiency of dairy cattle provides a significant relationship to the measured parameter. Relationship between breeders age (0.018<0.05) significant; significant relationship between breeding experience (0.041<0.05); relationship the level of knowledge (0.012<0.05) is significant; relationship of education level (0.049<0.05) significant; the relationship between the training that breeders followed (0.233>0.05) was significant; relationship between the number of livestock owned by farmers (0.032<0.05) is significant; and significant influence between farmer skills (0,000<0,05). The study concluded that the results of the study showed that the higher the skill of the respondent / rancher, the higher the level of reproduction efficiency of cattle dairy cattle. It is recommended that training be carried out continuously in the long term as well conduct regular meetings to provide guidance, direction, and protect farmers.